Mali : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria-Staff Report; and Press Release on the Executive Board Consideration. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Mali's economy is showing renewed momentum resulting from a strong 2005-06 cereal harvest and strengthening terms of trade. The fiscal program remained well on track through end-2005. Discussion of the macroeconomic outlook focused on production-side growth prospects, such as rising international gold prices that would boost tax revenues and accelerate the mining sector's exploration and production capacity. Plans to strengthen the management of both tax exemptions and reimbursements will address tax administration weaknesses. In the banking sector, nonperforming loans rose from 20 percent to 28 percent of total loans.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet